COLLEGE STUDENTS' CHEATING BEHAVIORS - (:unkn) unknown (SOC PERSONALITY RES INC, 2014)
I explored the reasons given by college students for cheating during scholastic examinations. The participants were 26 students from Marmara University in Turkey. It was observed that most of the students identified cheating as taking reminder notes into an examination, getting help during the examination, or theft of knowledge. The tendency to cheat in a variety of ways was found to be high, particularly with regard to the preparation of cheating materials before the examination. While some students justified helping friends they are close to or who they observe as having difficulties, others considered it immoral and refused to be involved in the activity of cheating. Lastly, students generally did not feel regret if the examination consisted of questions where the answers depend solely on memorization or if there was a common belief that the lesson would have no use for their future career or lives.
Keywords: college students; academic dishonesty; cheating; plagiarism; scholastic examinations; ATTITUDES; PERCEPTIONS; DISHONESTY